Grape-Derived Polyphenolics Prevent Aβ Oligomerization and Attenuate Cognitive Deterioration in a Mouse Model of Alzheimer's Disease - Wang, Jun (Society for Neuroscience, 2008)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive impairments in memory and cognition. Extracellular accumulation of soluble high-molecular-weight (HMW) Aβ oligomers has been proposed to be largely responsible for AD dementia and memory deficits in the Tg2576 mice, a model of AD. In this study, we found that a naturally derived grape seed polyphenolic extract can significantly inhibit amyloid β-protein aggregation into high-molecular-weight oligomers in vitro. When orally administered to Tg2576 mice, this polyphenolic preparation significantly attenuates AD-type cognitive deterioration coincidentally with reduced HMW soluble oligomeric Aβ in the brain. Our study suggests that grape seed-derived polyphenolics may be useful agents to prevent or treat AD.